Designing Management Information System for Al-Ikhlas Mosque Activities in Kota Pari Village Using Waterfall Method - Hermansyah, Hermansyah; Wijaya, Rian Farta; Utomo, Rahmad Budi (International Conference on Sciences Development and Technology, 2022)
This research aims to address the issues faced in the management of activities at Al-Ikhlas Mosque in Kota Pari Village. Currently, the management of mosque activities is still done manually using notebooks and notice boards, which often lead to errors and delays in providing information to the congregation. Additionally, the management of mosque funds and activities is also less effective due to a lack of coordination between the mosque administrators and the congregation. To overcome these problems, this research is expected to produce a mosque activity management information system that can be used to manage mosque funds, activity schedules, and others. The Waterfall method is chosen as it is suitable for structured and well-defined system development projects. This method consists of stages such as analysis, design, implementation, testing, and maintenance. The result of this research is a management information system for Al-Ikhlas Mosque in Kota Pari Village, which can be used to manage mosque funds, activity schedules, and others. The system is designed to facilitate the management of mosque activities and provide accurate and timely information to the mosque congregation. Moreover, the system can also be utilized to enhance coordination between mosque administrators and the congregation. It is expected that the implementation of this system will improve efficiency and effectiveness in managing mosque activities.